(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the frequency of various gynecological cancers at a tertiary care hospital. Study Design: Cross sectional study. Place and Duration of Study: This study was conducted at the Department of Obstet and Gynae, Sheikh Zayed Hospital, Rahim Yar Khan from January 2018 to December 2018. Materials and Methods: In this study, the females with age more than 30 years irrespective of their gravida and parity presenting with per vaginal bleeding were included. All these cases underwent biopsy under direct vision and assessed for its results on histopathology for various malignancies. Results: In this study, 50 cases with positive malignancy outcome were selected. The mean age of the participants was55.67±13.31 years and mean duration of symptoms was 7.45±1.61months. Out of 50 cases, only 32% were educated, 84% wee from rural population and 10% were smokers. Out of 50 cases cervical malignancy was seen in 26 (52%), ovarian in 15 (30%) and endometrial or uterine in 9 (18%) of the cases. Conclusion: Gynecological malignancies are not that rate and the cervical cancer isthe commonest CA detected followed by ovarian carcinoma.